Introduction to differential equations - Taylor, Michael Eugene 1946- (AMS American Mathematical Society, 2022)
"The pdf contains a draft title page, draft copyright page and a draft manuscript"--
Includes bibliographical references and index
Keywords: Gewöhnliche Differentialgleichung; Differential equations; Ordinary differential equations -- Instructional exposition (textbooks, tutorial papers, etc.); Ordinary differential equations -- General theory -- Initial value problems, existence, uniqueness, continuous dependence and continuation of solutions; Ordinary differential equations -- General theory -- Linear equations and systems, general; Ordinary differential equations -- General theory -- Nonlinear equations and systems, general